Strengthening the International Monetary System : Exchange Rates, Surveillance, and Objective Indicators - Crockett, Andrew (Occasional Papers; Occasional Paper ;, 1987)
This report comprises three papers written by staff members of the Fund's Research Department on issues arising out of the reports on the international monetary system prepared in 1985 by the Group of Ten (representing the industrial countries participating in the General Arrangements to Borrow) and the intergovernmental Group of Twenty-Four on International Monetary Affairs. These two reports, which appear as appendices to this volume, were transmitted to the Interim Committee of the Fund's Board of Governors and were subsequently discussed by the Fund's Executive Board in early 1986.